2008
DOI: 10.1016/j.jacc.2008.08.047
|View full text |Cite
|
Sign up to set email alerts
|

The ELAPSE (Evaluation of Long-Term Clopidogrel Antiplatelet and Systemic Anti-Inflammatory Effects) Study

Abstract: Our pilot study showed no attenuation of clopidogrel's effects on platelet aggregation with long-term administration. However, platelet activation receptor expression increased with time and should be further evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 9 publications
4
40
1
2
Order By: Relevance
“…20 In one study of clopidogrel-native patients undergoing coronary stenting, clopidogrel treatment was associated with stable sCD40L levels at day 1 and at month 1 of treatment, and with significantly lower levels at months 6 and 12. 37 In our study, levels of sCD40L were slightly lower at discharge but similar to baseline at 4 weeks.…”
supporting
confidence: 71%
“…20 In one study of clopidogrel-native patients undergoing coronary stenting, clopidogrel treatment was associated with stable sCD40L levels at day 1 and at month 1 of treatment, and with significantly lower levels at months 6 and 12. 37 In our study, levels of sCD40L were slightly lower at discharge but similar to baseline at 4 weeks.…”
supporting
confidence: 71%
“…Detailed baseline demographic characteristics of these 26 patients have previously been reported (17 ). Of the 7 patients who stopped prematurely (4 before the 1-month visit, and 3 before the 6-month visit), 2 had contraindications to long-term dual antiplatelet therapy (nosebleed and surgery for colon cancer).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, we conducted a prospective study to investigate the longterm effects of aspirin and clopidogrel in CAD patients undergoing percutaneous coronary intervention (PCI). We found no general tendency toward development of CLR or ALR during long-term therapy, as assessed by LTA and VerifyNow methods (17 ). We compare 3 platelet-function tests (LTA, VerifyNow, and TEG assays) to evaluate their agreement in assessing and classifying ALR and CLR during long-term follow-up.…”
mentioning
confidence: 88%
“…Several previous studies demonstrated anti--inflammatory effect of low doses of ASA and clopidogrel, mainly in patients with CAD [18][19][20][21][22][23][24][25]. The results of subanalysis of Physician's Health Study suggested that cardioprotective effect of ASA correlated with its anti-inflammatory effect [26].…”
Section: Discussionmentioning
confidence: 96%